1996
DOI: 10.1063/1.871790
|View full text |Cite
|
Sign up to set email alerts
|

Fluid models for kinetic effects on coherent nonlinear Alfvén waves. I. Fundamental theory

Abstract: Collisionless regime kinetic models for coherent nonlinear Alfvén wave dynamics are studied using fluid moment equations with an approximate closure anzatz.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 30 publications
(64 reference statements)
1
61
1
Order By: Relevance
“…Many of the features of the waves were noted in the results. More recent theoretical work on the evolution of nonlinear Alfvén waves have been performed by Medvedev and Diamond (1996), Medvedev et al (1997), Goldstein et al (1999), Hollweg (1999, 2001), and Buti et al (1999Buti et al ( , 2001). These works were again able to show many of the observed features of the nonlinear waves, but also predicted many effects not found in the solar wind data.…”
Section: Final Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the features of the waves were noted in the results. More recent theoretical work on the evolution of nonlinear Alfvén waves have been performed by Medvedev and Diamond (1996), Medvedev et al (1997), Goldstein et al (1999), Hollweg (1999, 2001), and Buti et al (1999Buti et al ( , 2001). These works were again able to show many of the observed features of the nonlinear waves, but also predicted many effects not found in the solar wind data.…”
Section: Final Commentsmentioning
confidence: 99%
“…Interplanetary Alfvén waves have been shown to be dispersive and compressive (Medvedev and Diamond, 1996;Medvedev et al, 1997;Vasquez and Hollweg, 2001;Buti et al, 2001). Theoretical models such as Medvedev and Diamond (1996) and Medvedev et al (1997) have indicated that mode coupling between Alfvén waves and ion acoustic waves would result in heating of the local solar wind plasma via damping of the ion acoustic waves. The magnitude of this coupling and therefore the rate of energy transport from Alfvén wave energy to plasma thermal energy is presently unclear however.…”
Section: Introductionmentioning
confidence: 99%
“…Khabibrakhmanov et al (1993) developed a model of collisionless parallel shock based on a modified DNLS by including the anisotropy of the plasma distribution function and higher-order dispersion; the number of adiabatically reflected ions define the threshold conditions of the fire-hose and mirror-type instabilities in the upstream and downstream regions of the shock. Medvedev and Diamond (1996) modeled the kinetic resonant particle effects of nonlinear Alfvén waves by incorporating an additional term representing dissipation akin to parallel heat conduction in a modified DNLS, which removes the singularity usually encountered in the nonlinear terms of DNLS and takes into account nonlinear coupling of an Alfvénic mode to a kinetic ion-acoustic mode; damping of nonlinear Alfvén waves appears via a strong Landau damping of the ion-acoustic waves. Baumgartel (1999) applied the magnetically rarefactive (dark) MHD soliton solution of DNLS to explain magnetic holes observed in solar wind, planetary magnetosheath and cometary environment.…”
Section: Derivative Nonlinear Schrödinger Equationmentioning
confidence: 99%
“…Solitons in the magnetoplasma were studied theoretically using Derivative Nonlinear Schrödinger (DNSL) equation by several authors (Hada et al, 1989;Mjølhus and Wyller, 1988;Spangler, 1990;Medvedev and Diamond, 1996;Nocera and Buti, 1996;Buti, 1999;Passot et al, 2005) The solutions concerned mainly circularly polarized waves propagating parallel to the magnetic field. Another development concerned quasi-perpendicular propagation of dispersive Alfvén waves and processes leading to establishment of filamentary structures with small size perpendicular to B (e.g.…”
Section: Other Theoretical Models For Dispersive Alfvén Waves and Solmentioning
confidence: 99%
“…Alfvénic soliton solutions have been studied extensively using Derivative Nonlinear Schrödinger (DNSL) equation (Hada et al, 1989;Medvedev and Diamond, 1996;Mjølhus and Wyller, 1988;Nocera and Buti, 1996;Spangler, 1990;Buti, 1999;Passot et al, 2005), or complete one-or two-fluid equations (McKenzie et al, 2004;Dubinin et al, 2003Dubinin et al, , 2005Sauer et al, 2003). However, until recently it has not been realized that soliton solutions represent bipolar electric field structures with either positive Published by Copernicus Publications on behalf of the European Geosciences Union and the American Geophysical Union.…”
Section: Introductionmentioning
confidence: 99%